THE RELATIONSHIP OF CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITIES AND CORPORATE FINANCIAL PERFORMANCE IN ONE CONTINUUM - Etty Murwaningsari (Universitas Trisakti, 2010)
This study aims to identify the impact of Good Corporate Governance, represented by institutional ownership and managerial ownership, on Corporate Social Responsibility and Corporate Financial Performance.It examines 126 manufacturing companies listed at the Indonesian Stock Exchange (IDX) and have issued audited financial statements for 2006. The statistical method used to test the hypothesis is Path Analysis. The main results suggest that Good Corporate Governance has effects on both Corporate Social Responsibility and Corporate Financial Performance whereas Corporate Social Responsibility has significant effects on Corporate Financial Performance. The other results regarding controlling variables suggest that CEO Tenure, has significant effects on Corporate Social Responsibility. Yet, there is no strong evidence to support that types of industry serve as an influencing factor on Corporate Social Responsibility as well as no influence of Corporate Secretary and Nomination and Remuneration Committee on Corporate Financial Performance.Keyword: corporate governance, corporate social responsibilities, corporate financial performance, Tobin's Q, institutional ownership, managerial ownership.